Microbial niches in raw ingredients determine microbial community assembly during kimchi fermentation. (15th July 2020) - Song, Hye Seon; Whon, Tae Woong; Kim, Juseok; Lee, Se Hee; Kim, Joon Yong; Kim, Yeon Bee; Choi, Hak-Jong; Rhee, Jin-Kyu; Roh, Seong Woon
Highlights: We investigated the origin source of fermentative microbes of kimchi. The dominant fermentative microbial taxa differed according to the raw ingredients. Not all ingredients carried the microbes capable of processing kimchi fermentation. The origin-reflexed microbial community assembly led to distinct metabolic phenotypes. Abstract: Fermented foods constitute hubs of microbial consortia differentially affecting nutritional and organoleptic properties, quality, and safety. Here we show the origin source of fermentative microbes and fermentation dynamics of kimchi. We partitioned microbiota by raw ingredient (kimchi cabbage, garlic, ginger, and red pepper) to render kimchi fermented by each source-originated microbe pool and applied multi-omics (metataxonomics and metabolomics), bacterial viability, and physiochemical analyses to longitudinally collected samples. Only kimchi cabbage- and garlic-derived microbial inoculums yielded successful kimchi fermentations. The dominant fermentative microbial taxa and subsequent metabolic outputs differed by raw ingredient type: the genus Leuconostoc, Weissella, and Lactobacillus for all non-sterilized ingredients, garlic, and kimchi cabbage, respectively. Gnotobiotic kimchi inoculated by mono-, di-, and tri- isolated fermentative microbe combinations further revealed W . koreensis -mediated reversible microbial metabolic outputs. The results suggest that the raw ingredient microbial habitat niches selectively affect microbial community assembly patterns and processes during kimchi fermentation.